Economic Viability of Beef Farms Under Different Country-Specific Production Systems: An Analysis Based on Agri Benchmark Network Data (2014-2023) - Artur WILCZYNSKI; Ewa KOLOSZYCZ (Communications of International Proceedings, 2025)
The beef sector faces numerous challenges, including societal pressures for sustainability, growing competition from meat substitutes, and changing consumer preferences. Consequently, greater efficiency, sustainability, and adaptation to the demands of increasingly conscious consumers have become critical factors for ensuring the long-term success of beef farms. This study aimed to evaluate the viability and economic condition of beef farms operating under four distinct production systems. The research utilized typical farm data collected and processed by the agri benchmark Beef and Sheep Network. To assess economic condition and viability, two specific indicators were employed: the pure farm condition index and the pure farm economic viability index. Data from 2014 to 2023 were analysed. The results showed that the highest economic condition index was observed in typical farms operating under the highly intensive Grain-fed beef finishing production system. These farms were located in Argentina, Australia, Spain, China, Tunisia, and Morocco. However, this did not necessarily equate to the highest economic viability. Instead, the highest economic viability index values were observed in farms utilizing the extensive Pasture production system. This group included beef farms from Argentina, Brazil, Colombia, Uruguay, Paraguay, Australia, Ireland, and England. These findings suggest that farms in this category have the greatest capacity to adapt to a rapidly changing environment and a higher potential for long-term development.
Keywords: economic viability index; typical farms; economic analysis of beef production; international compare of beef systems